Citizens as experts in a Greek political audience discussion program. (September 2016) - Patrona, Marianna
Abstract: This article sets out to explore the type of discourses produced by participating citizens in a Greek political audience discussion program, capitalizing on different aspects of the economic crisis that has afflicted Greece since 2010. Departing from the dichotomy between abstract, expert talk and the ordinary discourse of personal experience postulated in the 1990s, and the subsequent transformations of 'ordinariness' in current broadcast output, this paper examines the situated performances of citizens in a concrete political broadcast format at a particular moment in time. This moment is characterized by economic crisis, as the overarching societal condition which legitimizes ordinary expertize by endowing citizens with increased conversational rights, compared to what is typical of citizen participation in political panel discussions with an audience in other European contexts, and the entitlement to engage in authoritative forms of talk. By drawing on discourse analysis and conversation analysis of sequences of TV talk, the analysis unveils the rhetorical strategies, as well as the evidential devices and forms of knowledge projected in citizen talk. Finally, the article calls attention to the implications of these forms of discursive participation for empowering the role of citizens in political communication, public dialog and democratic debate.